Pengenalan Teknik PCR (Polymerase Chain Reaction) untuk Meningkatkan Kompetensi Guru Biologi pada Tingkat SMA di Kalimantan Selatan - Dindin Hiayatul Mursyidin; Yudhi Ahmad Nazari; Deni Setiawan; Ridho Hairil Herdin Prasetyo; Nazrin Wahidi (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
High school teachers as educators are highly demanded to have high competence in the scientific field, especially molecular biology, to improve the quality of education and the students they educate. However, the weak or gaps in knowledge and mastery of molecular biology material among high school biology teachers in various regions have prompted the need for intensive assistance to improve this. Hence, this activity aims to introduce PCR (polymerase chain reaction) analysis techniques as part of molecular biology materials to upgrade the competence and professionalism of high school biology teachers in Banjarbaru City and Banjar Regency, South Kalimantan. Technically, the activities are divided into two sessions, i.e., (1) general lectures to explain the basic concepts of PCR analysis and their applications and (2) hands-on practice of PCR analysis in the Genetics and Molecular Biology Laboratory of FMIPA ULM. In this activity, there were 14 participants consisting of biology teachers from several high schools in Banjarbaru City and Banjar Regency, South Kalimantan. Generally, the activities ran smoothly, and they were enthusiastic from the beginning to the end of the session. The evaluation showed that the knowledge and skills of teachers were increasing. However, similar or further activities (continuation) to improve the understanding of the concepts and practices of these teachers regarding molecular biology analysis are also necessary.